Effect of baseline eicosapentaenoic omega 3/omega 6 fatty acids ratio on COVID-19 severity in non-immunized patients - Fernandes, Ligia Prestes (2023)
Since the beginning of the SARS-CoV-2 pandemic, a strong association has been observed between excessive production of pro-inflammatory cytokines and the severity of COVID-19. ln this context, anti-inflammatory drugs have been widely used to alleviate symptoms and improve the prognosis of patients. Several studies indicate that a higher proportion of omega-3 fatty acids, especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), compared to omega-6 fatty acids such as arachidonic acid (AA), contributes to the resolution of inflammatory processes by altering the profile of oxylipins and reducing the synthesis of prostaglandin E2 (PGE2). Based on this premise, the objective of this study was to evaluate whether a higher EPA+DHA/AA ratio at the time of viral infection could be associated with lower production of pro-inflammatory cytokines via a reduction in PGE2 and, consequently, a better prognosis for patients. To test this hypothesis, blood samples were collected from 180 unvaccinated patients diagnosed with COVID-19, admitted to public hospitals in the city of São Paulo between July 5, 2020, and September 17, 2020. The patients were classified into categories 1 to 5, progressively increasing according to the severity of the disease during hospitalization. Fatty acids and oxylipins were quantified using chromatography coupled with mass spectrometry. The results showed that Group 1 had a higher EPA/AA ratio than Group 5 (p = 0.010), confirming the hypothesis, although in terms of EPA and not omega-3 (p = 0.276). It was also observed that this result was accompanied by a higher concentration of pro-inflammatory cytokines, especially IL-6 (p=0.002) and C-reactive protein (p<0.001). However, this anti-inflammatory effect was not associated with the concentration of PGE2. Patients in Group 1 also had a lower concentration of F2-isoprostanes, an important biomarker of oxidative stress, compared to Group 4 (p=0.009). This result appears to be more associated with a probable effect of inflammation reduction. It can be concluded that a higher EPA/AA ratio at the time of viral infection was associated with a lower concentration of inflammatory cytokines and a milder severity of the disease. However, further studies are needed to identify the mechanism of this effect, emphasizing that the EPA/AA ratio is a modifiable factor in the diet, and other infections that involve excessive production of pro-inflammatory cytokines may occur again.